Implementa??o de medi??es automatizadas de interfer?ncias eletromagn?ticas - Magalh?es, Gilberto Vilas Boas (2008)
Electromagnetic compatibility (EMC) is the capability of an electrical device or system to operate in its electromagnetic environment, without disturbing or being disturbed by it. The aim of this thesis is to study the electromagnetic susceptibility, and electromagnetic interference experiments, developing software to measure the radiation and conducted emission. A predominant factor for the development programs in measurements of radiated and conducted emission relates with sweep time, applying quasi peak and average detectors for the signal measured through the spectrum analyzer. That equipment was available and used as a reference one. Domestic and international standards show the values and frequency range for the experiment, determined with the detectors, specified for each case. As the level with the peak detector is always greater or equal to the obtained with quasi peak and average detectors, there is a possibility to make experiment. It takes place by using the peak detector, whose sweep time is less than the other type. A developed program using LabViewTM compares the measurements among the specified limit. If exceeding, this value would perform the measurement only for those frequencies. For the conducted emission, it is determined the disturbances at the power supply wires, with the line impedance stabilization network (LISN) connected to the spectrum analyzer. The radiation emissions are performed with the equipment under test inside the anechoic chamber, in a known distance from the antenna. The electric field intensity is determined from antenna data sheet that includes the gain and antenna factor, it must be calibrated. These data are used by programs to convert the measurement level to electric field intensity.